2015
DOI: 10.1088/0957-4484/26/30/304003
|View full text |Cite
|
Sign up to set email alerts
|

Control of the initial growth in atomic layer deposition of Pt films by surface pretreatment

Abstract: The controllability of the nucleation behavior of Pt in atomic layer deposition (ALD) by surface pretreatments with H2O, H2S, and NH3 was investigated. The H2O pretreatment on SiO2 and TiO2 surfaces had little effect on the nucleation of Pt. The H2S pretreatment on the SiO2 and TiO2 surfaces significantly delayed the nucleation of Pt on them, while the NH3 pretreatment on the TiO2 surface led to fluent nucleation of Pt. In particular, a continuous Pt film was successfully formed even at an ultrathin thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Furthermore, here we did not explore the effect of surface modifications prior to ALD. Previous studies have already shown that tailored surface pretreatments can be instrumental not only to the onset of precursor chemisorption but also to the mitigation of metal aggregation . While the initial state of the surface of the support is crucial for the whole ALD process, our results also emphasize how the sequential exposure to different reacting environments induces periodic changes in the metal–support interaction, whose nature and extent are a strong function of the operating conditions.…”
Section: Final Remarks and Outlooksupporting
confidence: 57%
“…Furthermore, here we did not explore the effect of surface modifications prior to ALD. Previous studies have already shown that tailored surface pretreatments can be instrumental not only to the onset of precursor chemisorption but also to the mitigation of metal aggregation . While the initial state of the surface of the support is crucial for the whole ALD process, our results also emphasize how the sequential exposure to different reacting environments induces periodic changes in the metal–support interaction, whose nature and extent are a strong function of the operating conditions.…”
Section: Final Remarks and Outlooksupporting
confidence: 57%
“…As most of the noble metal thin films prepared by ALD undergo incubation for nucleation growth, ,, the growth and electrical characteristics can be influenced by the growth mechanism during the initial stage of growth with the transition regime, the outmost surface changes from the substrate surface to the final saturated and continuous surface of the metal film. , Therefore, we conducted a careful study to understand the growth mechanism of Pt thin films. Figure a shows the variation of Pt thin film thickness (determined by FE-SEM) depending on the ALD cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, noble metals by the ALD process suffer from poor nucleation due to the difference in surface energy between the substrate and metals, which can influence the growth characteristics. Additionally, the composition and electrical properties of noble metal thin films can be modified by using other counter reactants and gas-phase electron activation. Therefore, by using the above Pt precursors, the effects of various deposition parameters, such as pretreatment and different reactants, such as O 3 generated from ozone generators and plasmas, have been studied to improve the growth behavior and functional properties of Pt thin films, , which is highly desired to improve the performance in microelectronic devices and catalysis. Thus, the development of ALD Pt films with improved electrical and growth characteristics without additional treatments is still a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…However, in light of a few reported FBR-ALD studies 21,38 , the synthesis of a FBR Pt catalyst through a process with increased efficiency and speed, and an improved fluidizing behavior is highly desired. In addition, the growth behavior of the ALD process also strongly depends on the surface conditions [39][40][41] , which can affect the uniformity, particle size and density of the Pt NPs toward improving the electrochemical surface active area (ECSA) and durability. However, the effect of the carbon support on Pt formation based on wet processing has been intensely studied despite the different growth mechanisms between the wet process and ALD 14,19 .…”
Section: Introductionmentioning
confidence: 99%